2013
DOI: 10.1097/mpa.0b013e318279fe5c
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis-Associated Ascitic Fluid Induces Proinflammatory Cytokine Expression in THP-1 Cells by Inhibiting Anti-inflammatory Signaling

Abstract: Pancreatitis-associated ascitic fluid up-regulated proinflammatory cytokines by interfering with proinflammatory and anti-inflammatory signaling pathways, thus exacerbating activation in acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…As is known, PAAF plays an important role during the progression of SAP. It contains a mass of toxic substances including tumor necrosis factor a, interleukin and endotoxin, which can induce pancreatic tissue necrosis and aggravate the inflammatory response [2][3][4][5]. Therefore, various treatment strategies that remove PAAF may be effective in treating SAP [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is known, PAAF plays an important role during the progression of SAP. It contains a mass of toxic substances including tumor necrosis factor a, interleukin and endotoxin, which can induce pancreatic tissue necrosis and aggravate the inflammatory response [2][3][4][5]. Therefore, various treatment strategies that remove PAAF may be effective in treating SAP [25].…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic associated ascites fluid (PAAF) is known to play a critical role in the pathogenesis of SAP because it contains various Chen Luo and Qilin Huang have contributed equally to this study. toxic substances such as tumor necrosis factor, interleukin, endotoxin and so on [2][3][4][5]. Our previous clinical and experimental studies showed that abdominal paracentesis drainage (APD) attenuated the outcomes of SAP safely and effectively through removing PAAF [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the activation of PPAR␥ in immune cells may inhibit NF-B activation and further lead to the downregulation of proinflammatory cytokine expression. Using pancreatitis-associated ascitic fluid to treat THP-1 cells, a human monocytic cell line, the levels of NF-B-p65 and proinflammatory cytokines (i.e., TNF-␣ and IL-6) were increased, whereas the downregulation of PPAR␥ was observed (Wang et al 2013a). Pretreatment with pioglitazone, a ligand of PPAR␥, could protect rats from acute pancreatitis through the downregulation of NF-Binduced proinflammatory cytokines (TNF-␣ and IL-6) .…”
Section: Fig 2 Effects Of a Membranaceus On The Antibody Levels Ofmentioning
confidence: 96%
“…NF-κB and p38MAPK are the two main signaling pathways activated by TLR4-mediated signaling, and both play an important role in the regulation of several inflammatory cytokines and mediators. Previous work from our group has shown that the activation of NF-κB and p38MAPK is a prominent response during pancreatic injury and that activation of these molecules plays a key role not only in the release of inflammatory factors, but also in increasing neutrophil infiltration of the pancreas (14,26). All the above research thus suggests that TLR4 plays an important role in the synthesis and release of proinflammatory cytokines, and indicates that upregulation of the TLR4 gene may be related to the development of inflammation in SAP.…”
Section: Discussionmentioning
confidence: 96%
“…It is well known that NF-κB and p38MAPK play critical roles in regulating the expression of proinflammatory genes such as TNF-α, IL-β and IL-6 (11,12). Our previous findings indicated that these two signaling pathways were activated in SAP rats (2,13) and pancreatitis-associated ascitic fluid stimulated THP-1 cells (14), which was suppressed by wortmannin (2). In the present study, we examined the expression of TLR4, PI3K, Akt, p38MAPK, NF-κBp65 and MyD88 in vivo in SAP rats and in vitro in RAW264.7 murine macrophages (stimulated by LPS) following treatment with the PI3K agonist insulin-like growth factor (IGF)-1, and further explored the possible mechanisms by evaluating the correlation between PI3K/Akt and TLR4 in inflammatory reactions associated with SAP.…”
Section: Introductionmentioning
confidence: 93%